Город в палестинской гражданско-храмовой общине VI-IV вв. до н.э. - Вейнберг, И. П. (1973)
Weinberg, J. Р.; The Palestinian civic- and temple community of the 6th-4th centuries B.C.; engl. Résumé S. 234.